Інформаційно-аналітичне забезпечення управління виробництвом продукції органічного землеробства - Гузь, Михайло Михайлович (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня кандидата економічних наук зі спеціальності 08.00.09 «Бухгалтерський облік, аналіз та аудит (за видами економічної діяльності)». Національний університет біоресурсів і природокористування України. Київ, 2021. Дисертація спрямована на вирішення проблеми інформаційно-аналітичного забезпечення управління виробництвом продукції органічного землеробства. Досліджено теоретичні засади інформаційно-аналітичного забезпечення управління виробництвом продукції органічного землеробства, зокрема обґрунтовано сутність органічного землеробства, охарактеризовано систему показників аналізу та прогнозування його розвитку, розглянуто особливості формування інформації для аналітичного забезпечення управління виробництвом продукції органічного землеробства. Запропоновано авторські визначення (уточнення) понять: «органічне землеробство», «натуральна продукція», «органічна продукція», «екологічна продукція». Оцінено інформаційно-аналітичне забезпечення формування конкурентоспроможного органічного землеробства. Розглянуто чинники формування ефективного органічного землеробства в Україні, проаналізовано стан і тенденції виробництва продукції органічного землеробства, проведено оцінку релевантності інформації для управління стратегічним розвитком органічного землеробства. Запропоновано концептуальні напрями вдосконалення інформаційно-аналітичного забезпечення управління розвитком органічного землеробства на основі розробленої імітаційної моделі інноваційно-інвестиційного розвитку підприємств органічного землеробства.
The dissertation for obtaining a scientific degree of candidate of economic sciences from the specialty 08.00.09 «Аccounting, analysis and audit (for types of economic activities)». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2021. The dissertation is devoted to the disclosure of the methodological principles of information and analytical support for the production of production of organic agriculture products and the development of practical measures for its introduction. According to the results of the study of the theoretical principles of the development of alternative methods of agricultural production, the definition of «organic farming» category is specified. This is a system of management of reproducing agro-processes based on the maximum use of biological factors for increasing soil fertility and plant protection, as well as the implementation of a set of measures that provide bio-socio-economic production of organically safe products. Three types of organic products are delimited. Natural (farm) is a product made of conventional raw materials and using a traditional soil cultivation, but without the use of synthetic and chemicals. Organic certified products are products that take into account not only direct stages of production, but also secondary channels of forming its quality. Environmental products - fully meet the requirements of organically safe, but its life cycle involves taking into account the environmental impact. The system of information and analytical elements of evaluation of organic agriculture has been formed. This is the synthesis of its common elements (ecosystem, natural resources, health and well-being) and information flows of the management process of consumers, agroharch chain, manufacturers and state policies, oriented on compliance with economic and social criteria and environmental principles. A component matrix assessment of the system of information and analytical provision of management of organic farming is developed. The matrix summarizes the information needs of the consumers of organic products and other market entities, agrarian manufacturers, public administration and local self-government bodies, other institutions involved in the development of organic agriculture, as well as the principles of sustainable development of agrarian formations, control and analytical capabilities of accounting systems. An analysis of the state and trends of production of organic agricultural products are carried out. The Ukrainian market develops under the influence of world trends. If Europe or the United States grows an area of organic and selling such products, then there is an ascending trend in Ukraine. Over the past five years, the area of organic agricultural land in Ukraine has increased by 1.5 times. And the growth rates of organic production are 5.5 times higher than in Europe and 4.9 times – than in the world. This is despite the fact that in Ukraine organic lands occupy 1.1 % of 42.7 million hectares of agricultural land. The factors of development of effective organic agriculture in the world and Ukraine are systematized. This is the state and quality of existing natural resource potential, its sectoral component, power and intensity of assimilation processes, which is implemented under the influence of reproduction laws using existing agricultural formation factors. The key management indicators of the functioning of effective organic agriculture are: proper normative support; state support for development; the complexity of the process of organic production through the inter-sectoral cooperation of plant growing and livestock, observance of organizational and technological requirements of production. The system of information and analytical support for the production of production of organic agricultural products is a set of organizational, legal, accounting, analytical, control, industrial, technological, innovative, investment, social and environmental components. This ensures rational use and effective reproduction of the bioreysus potential of agrarian molds, based on the quality of managerial decisions due to the balance of information flows. The simulation model of the development of the organic farming system has been developed, the target function of which is optimizing the profit of enterprises. The constraints of the model are: well-founded crop rotation, the use of organic fertilizers and their introduction. The developed model is the basis of information and analytical support for the development of organic agriculture. The simulation model of management covers a generalized action system aimed at achieving the goal due to the effective use of resource potential, compliance with the requirements of the domestic legislative framework and international standards, as well as the norms of organic agricultural production. Priority directions for the effective implementation of the information and analytical model of production management of organic products are: increase of investment attractiveness of Ukraine as an image guarantor of domestic organic production; introduction of the register of operators of the organic market; sectoral isolation of information flows in the reporting of business entities in relation to organic production; consolidation of institutional principles of organic production in the accounting policies of enterprises; reflection in the accounting of high-quality land parameters and assimilation potential that determine the fair production value of organic products.
Keywords: облік; аналіз; управління; система інформаційно-аналітичного забезпечення; органічне землеробство; натуральна продукція; органічна продукція; екологічна продукція; імітаційна модель; компонентна матриця; аграрні формування; accounting; analysis; management; information and analytical support system